STUDY OF THE CLINICAL AND FUNCTIONAL STATE OF THE VISUAL ORGAN IN WOMEN WITH MILD MYOPIA DURING PREGNANCY AND THE POSTPARTUM PERIOD (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Hormonal changes occurring in the body during pregnancy, including cyclical fluctuations in estrogen and progesterone levels, as well as hemodynamic alterations, affect ocular tissues and microcirculation, leading to significant changes in intraocular pressure, retinal microcirculation, ocular muscle function, and accommodative capacity. According to global statistics, the prevalence of myopia among women with ocular diseases ranges from 25% to 35%, and transformations in visual function during pregnancy have been confirmed by statistical data (WHO, 2020).
Keywords: Recurrent pregnancy, laser coagulation, peripheral retinal dystrophies, mild myopia